Multiplexed detection of nuclear immediate early gene expression reveals hippocampal neuronal subpopulations that engage in the acquisition and updating of spatial experience - Hoang, Thu-Huong; Manahan-Vaughan, Denise (Frontiers in Integrative Neuroscience, 2025)
Acquired spatial representations are not static. Each re-exposure to the spatial environment stimulates retrieval of the stored experience followed by information re-encoding, including updating if the environment has changed. It remains unclear if the same neurons are involved in these three events. Here, we used a multiplexed fluorescence in situ hybridization (FISH) approach that detected “time-locked” nuclear immediate early gene (IEG) expression to identify hippocampal neuronal ensembles that were engaged in the acquisition of a spatial representation, as well as its subsequent stabilization and/or updating. Responses were assessed in distal CA1 (dCA1) and proximal CA1 (pCA1) of the dorsal hippocampus of male rats. Homer1a was used to detect neuronal recruitment triggered by novel learning of a holeboard environment (HB). cFos and Arc expression were used to detect ensemble stability and/or expansion, or ensemble remodeling, respectively, that was triggered by animal exposure to the now familiar HB that included novel objects (HBO) 25 min after the initial HB exposure. Novel HB exposure resulted in nuclear Homer1a expression in both dCA1 and pCA1. Subsequent HBO triggered significant cFos and Arc expression only in dCA1. IEG co-labeling (Homer1a/cFos, Homer1a/Arc and Homer1a/cFos/Arc) was also only evident in dCA1, reflecting both re-iteration and remodeling of dCA1, but not pCA1 ensembles.In sum, we show that the contiguous acquisition and updating of spatial representations recruits distinct populations of CA1-neurons reflecting ensemble selection and stabilization, as well as ensemble remodeling. Moreover, whereas dCA1 and pCA1 are involved in the acquisition of the original spatial representation, only dCA1 is engaged in representation updating related to changes in spatial content information.